Fanaticism of a Korean Boy Band, â€œShineeâ€ as Perceived by K-Popers â€œShinee World Indonesiaâ€ in Karawang Regency - Abidin, Zainal; Tayo, Yanti; ., Mayasari (International Journal of Engineering and Technology, 2018)
Korean popular music, or broadly known as K-Pop, is the most noticeable example of hallyu-wave products. Actors, actresses, soloists, duos, and groups consisting of several members are considered as K-Pop performers. In Korea, such performers are popular by the term â€œidolâ€. Those who idolize a particular idol, whether it is soloist or group, often join a fans-club called â€œfandomâ€. Teenagers as common members of fandom will identify and try to behave in similar way to their idols. Looking at that phenomenon, this study aims to find the motive behind K-Popers â€œSHINee World Indonesiaâ€ fanaticism of a Korean boy band, SHINee.This study applies qualitative method, a research method which is defined as an attempt to get a better understanding regarding the complexity of human interaction. It results in several keywords of qualitative research: process, understanding, complexity, interaction, and human. The researchers adopt qualitative method with phenomenology approach, due to the fact that the research object is closely related to the motive behind K-popers fanatics and their imitative behavior. The researchers realize that the motive and imitative behavior of K-Popers fanatics are processed within themselves, not by the visible behaviors in the outside.This phenomenology research tries to gain knowledge regarding how an early fan constructs the important meaning and concepts in inter-subjectivity frame. Fanaticism process is triggered by a motive which is divided into four reasons: (1) generating interest, (2) knowledge, (3) satisfaction, and (4) absorbing â€œSHINeeâ€ as a part of fanaticism lifestyles.Â Â